Synergistic metabolism of Lactobacillus and yeast at different inoculation improves the quality of fermented beef - Liu, Xiaoxia; Li, Xiang; Lian, Zeyuan; Lv, Pengjian; Luo, Aiguo (Frontiers in Microbiology, 2026)
BackgroundFermented meat products rely on complex microbial interactions to develop desirable safety, nutritional and sensory attributes. Lactic acid bacteria and yeasts are among the most frequently used starter cultures, yet their individual and interactive contributions to physicochemical changes and metabolite formation remain incompletely understood. In particular, how different inoculation ratios of bacteria and yeast regulate acidification, nitrogen metabolism and lipid remodeling in fermented meat has received limited attention. Therefore, this study investigated the effects of single and co-fermentation by Lactobacillus plantarum and Debaryomyces hansenii at different inoculation ratios on physicochemical properties and the non-volatile metabolome of fermented meat.MethodsSix fermentation treatments were designed, including an uninoculated control (A), L. plantarum alone (B), D. hansenii alone (C), and co-inoculated systems with lactic acid bacteria to yeast ratios of 1:1 (D), 1:2 yeast-dominant (E), and 2:1 lactic acid bacteria-dominant (F). After fermentation, pH, protein content and total volatile basic nitrogen (TVB-N) were determined to evaluate acidification, protein accumulation and nitrogen degradation. Untargeted non-volatile metabolomics was performed, and differential metabolites among treatments were screened using orthogonal partial least squares discriminant analysis (OPLS-DA).ResultsCompared with the control (pH 6.01, protein 17.6 g per 100 g, TVB-N 8.4 mg per 100 g), L. plantarum fermentation markedly lowered pH to 4.72 and reduced TVB-N to 7.3 mg per 100 g. D. hansenii alone caused moderate acidification (pH 5.77), increased protein content to 21.9 g per 100 g, and resulted in a TVB-N level of 7.6 mg per 100 g. Co-fermentation showed clear ratio-dependent effects. Treatments D and F achieved lower pH values (4.55 and 4.45) with TVB-N levels of 6.2 and 5.6 mg per 100 g, respectively. The yeast-dominant treatment E exhibited the highest protein content (24.7 g per 100 g) and the lowest TVB-N (4.3 mg per 100 g). Metabolomics analysis identified 72 differential non-volatile metabolites, mainly lipids and nitrogen-containing compounds. Treatment E was characterized by increased free amino acids, phospholipids (e.g., LPC 18:2 and LPE 18:2), unsaturated fatty acids (linoleic and oleic acids), and nicotinic acid, whereas treatment F showed intensified phospholipid signals (e.g., PC 34:1) accompanied by depletion of multiple amino acids and nicotinamide.DiscussionThe results demonstrate that the inoculation ratio of L. plantarum and D. hansenii plays a decisive role in regulating acidification, proteolysis and lipid remodeling during meat fermentation. Yeast-dominant co-fermentation promoted protein accumulation and enrichment of unsaturated fatty acids, likely through enhanced proteolytic activity and lipid metabolism, while effectively limiting TVB-N formation. In contrast, lactic acid bacteria-dominant fermentation intensified acidification and further suppressed nitrogenous spoilage indicators, albeit with reduced amino acid availability. These findings highlight the importance of microbial balance in starter culture design and provide a mechanistic basis for tailoring fermentation strategies to simultaneously improve safety and sensory quality of fermented meat products.